GIS Automation for Spatialization of Water Availability - Bielenki Júnior, Cláudio (Universidade Federal do Rio de Janeiro, 2016)
The application of regionalization methods is one of the most important procedures for the estimation of the streamflow discharge in ungauged rivers catchments and its automation can reduce both processing time and susceptibility to errors. The Environmental Systems Research Institute (ESRI), in cooperation with the Center for Research in Water Resources at University of Texas (CRWR), has developed the ArcHydro toolset, a geospatial data model designed for hydrological models and used to accumulate attributes in the hydrographical net, among other functionalities. The present paper addresses the automation of the low flow index Q95 accumulation in the Doce River Basin by ArcHydro and the application of the regionalization method based on the proportionality of the ratio discharge per unit of drainage area. The effects of the reservoirs operation on water availability were computed automatically in this process and reliable results time savings were achieves.